Sistem Pengendalian Persediaan Barang pada Toko Mulia Jaya Elektronik Karawang - Muhammad Tandi Prasetyo; Wanta; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was motivated by a less than optimal inventory control system at the Mulia Jaya Elektronik store, in the process it may also have an impact on the security of stock. Procurement of merchandise at the Mulia Jaya Elektronik store does not yet use standard methods, procurement is still carried out using calculations based on estimates and there is a lack of control over the inventory of goods at the Mulia Jaya Elektronik Store. The purpose of this study is to analyze the appropriate inventory control system implemented at the Mulia Jaya Elektronik store. The inventory control method that researchers will use is the ROP (Reorder Point) method in procuring merchandise and increasing inventory security through inventory management. The work of writing this study article uses a quantitative descriptive method. The results of this research can make a positive contribution to better procurement of inventory goods through the implementation of an effective inventory control system.